Ensino em ciências: a avaliação da aprendizagem por meio do jogo didático - Reis, Vanda Renata (2014)
Due to the major changes occurring in our society, especially in the media (internet, mobile) becomes necessary to review the forms of teaching and learning so that we are able to adentar demand. Aiming to contribute to the learning process, this study used the games as a way of teaching evaluation, because through it, one can achieve various objectives such as development of intelligence and personality development of sensibility and the esteem, simulation of group life , involvement of action, challenge, curiosity and creativity. The educational games used were didactics crossword (where it worked the circulatory system, respiratory system, nervous system), set Glue (digestive system); Game "Race of sperm" and set passes or passes (Sexuality Reproductive System and Sexually Transmitted Diseases. The results obtained in this study allowed us to confirm the importance of using different classes for science teaching. Through various games, we realized how this methodology provided an opportunity to the students about effective learning of concepts (respiratory, circulatory, nervous, digestive, reproductive) systems and sexuality. We concluded that the educational games are featured on the merits to represent the play as the foundation of culture (most people played with crosswords, collages, board games and game passes or passes) and their modes of transmission rescuing dialogue between young and educators that make the learning process more enjoyable, attractive and efficient.